Sur la retraduction de Virgile en Angleterre au XVIIe siècle : les enjeux politiques et esthétiques de l'Enéide de John Ogilby (1654) - Marie-Alice Belle (Etudes Epistémè)
Immediately acclaimed as the fairest volume ever produced by the English press, the illustrated English edition of Virgil’s works published in 1654 by the Royalist translator John Ogilby stands at the apex of an unprecedented movement of retranslation of Virgil’s œuvre in England. As revealed by a comparative analysis of the textual, interpretive and aesthetic strategies at work in Ogilby’s translation of the Aeneid and other contemporary versions of the poem, Ogilby’s Aeneid can be defined as an « active retranslation » (Anthony Pym) of the Virgilian epic. Far from being merely determined by the linguistic, ideological or aesthetic norms of its times, Ogilby’s 1654 Aeneid can be best understood as a deliberate attempt at reviving the interpretive and aesthetic codes of Baroque Court culture as constructed by the Royalist public to which it was explicitly dedicated.